Implant-based multi-parameter telemonitoring of patients with heart failure and a defibrillator with vs. without cardiac resynchronization therapy option: a subanalysis of the IN-TIME trial - Geller, Johann Christoph; Lewalter, Thorsten; Bruun, Niels Eske; Taborsky, Milos; Bode, Frank; Nielsen, Jens Cosedis; Stellbrink, Christoph; Schön, Steffen; Mühling, Holger; Oswald, Hanno; Reif, Sebastian; Kääb, Stefan; et al. (Clinical research in cardiology, 2019)
AIMS: In the IN-TIME trial, automatic daily implant-based multiparameter telemonitoring significantly improved clinical outcomes in patients with chronic systolic heart failure and implantable cardioverter-defibrillator (ICD) or cardiac resynchronization therapy defibrillator (CRT-D). We compared IN-TIME results for ICD and CRT-D subgroups. METHODS: Patients with LVEF ≤ 35%, NYHA class II/III, optimized drug treatment, no permanent atrial fibrillation, and a dual-chamber ICD (n = 274) or CRT-D (n = 390) were randomized 1:1 to telemonitoring or no telemonitoring for 12 months. Primary outcome measure was a composite clinical score, classified as worsened if the patient died or had heart failure-related hospitalization, worse NYHA class, or a worse self-reported overall condition. RESULTS: The prevalence of worsened score at study end was higher in CRT-D than ICD patients (26.4% vs. 18.2%; P = 0.014), as was mortality (7.4% vs. 4.1%; P = 0.069). With telemonitoring, odds ratios (OR) for worsened score and hazard ratios (HR) for mortality were similar in the ICD [OR = 0.55 (P = 0.058), HR = 0.39 (P = 0.17)] and CRT-D [OR = 0.68 (P = 0.10), HR = 0.35 (P = 0.018)] subgroups (insignificant interaction, P = 0.58-0.91). CONCLUSION: Daily multiparameter telemonitoring has a potential to reduce clinical endpoints in patients with chronic systolic heart failure both in ICD and CRT-D subgroups. The absolute benefit seems to be higher in higher-risk populations with worse prognosis.
Keywords: senioři; Stroke Volume; Treatment Outcome; Telemedicine; Defibrillators, Implantable; telemedicína; výsledek terapie; Middle Aged; mužské pohlaví; příčina smrti; míra přežití; Prospective Studies; Německo; Follow-Up Studies; tepový objem; následné studie; ženské pohlaví; Humans; prospektivní studie; Survival Rate; Germany; defibrilátory implantabilní; lidé středního věku; Cardiac Resynchronization Therapy; systolické srdeční selhání; rizikové faktory; srdeční resynchronizační terapie; Female; Aged; Risk Factors; Heart Failure, Systolic; Cause of Death; lidé; Male